Beitrag zur Gattung Willemia Börner (Collembola). - Hüther, Walter (Contributions to Entomology = Beiträge zur Entomologie, 1962)
The morphology and chaetotaxy of 6 species of Willemia are studied. The arrangement of the bristles of the abdomen, especially that of Abd. IV and VI, is a good character to distinguish the species. - From Central America a new subspecies (W. buddenbrocki brevispina) is described. W. anophthalma, W. intermedia and W. scandinavica are redescribed (the first according to the types), and taxonomical additions are given for W. aspinata, W. persimilis and W. buddenbrocki buddenbrocki. - In a key all known species of the genus are enumerated. Nomenclatural Acts brevispina Hüther, 1962 (Willemia buddenbrocki), sspec. n.